Etika Bisnis Perspektif Al-Qur'an: Studi Komparatif Pemikiran Wahbah Zuhaili dan Muhammad Abduh - Muhayati, Muhammad Zulfi Hamdi; Fitri, Amiril Ahmad (Journal of Islamic Economic Studies, 2025)
This study aims to explore and compare the concept of business ethics from the perspectives of two prominent modern Islamic thinkers: Wahbah az-Zuḥaylī and Muhammad Abduh. The background of this research lies in the growing prevalence of unethical business practices in the modern era, despite ethics being a core pillar of the Islamic economic system. The study seeks to uncover normative and spiritual values that can serve as a foundation for building a just and sustainable Islamic economic framework. The research employs a qualitative method based on literature review, using primary sources such as Wahbah az-Zuḥaylī’s works (al-Fiqh al-Islāmī wa Adillatuh, al-Tafsīr al-Munīr) and Muhammad Abduh’s Tafsīr al-Manār, supported by secondary sources including books, journals, and scholarly articles. The analysis is conducted thematically and comparatively. Findings reveal that az-Zuḥaylī emphasizes legal-formal aspects such as fairness in transactions and proper documentation, while Abduh highlights spiritual awareness, moral consciousness, and social transformation in business practices. The study concludes that both approaches are complementary—az-Zuḥaylī reinforces the legal framework, whereas Abduh enriches the ethical and rational dimensions. These insights have theoretical and practical implications for contemporary Islamic business ethics policy development and open opportunities for further research in Islamic economics.